ANTECEDENTS OF THE ATTITUDE TO THE BRAND AND SELF-ESTEEM - Nurul Fadilah Aswar; Ilham Aksir, Asri Awal; Hartina Rosalia (ADISAM PUBLISHER, 2024)
This study aims to test the hypothesis about the factors that affect brand loyalty among Samsung smartphone users. This study is a quantitative research with primary data obtained through online questionnaires using Google Forms. A Likert scale with five points is used to measure the entire variable. The number of samples used was 100 respondents, where each indicator was represented by five respondents. Non-probability sampling techniques, especially purposive sampling, were used to select respondents who meet the criteria, namely Samsung smartphone users with a minimum of one year of use. Data analysis was conducted using Structural Equation Model (SEM) with SMART PLS program. Convergent validity is tested through outer loadings that must be greater than 0.70, while discriminant validity is tested through Average Variance Extracted (AVE) with a minimum value of 0.5. Reliability was tested using Composite Reliability and Cronbach's Alpha with a minimum value of 0.70. The results showed that brand satisfaction has a positive influence on attitudes towards brands and brand loyalty. In addition, love for the brand also has a positive effect on brand loyalty and self-esteem. However, self-esteem has no direct influence on brand loyalty. Attitudes toward brands served as a mediating variable in the relationship between brand satisfaction and brand loyalty, while self-esteem did not mediate the relationship between brand love and brand loyalty.